Optimal estimation of multi-country Gaussian dynamic term structure models using linear regressions - Antonio Díez de los Ríos (Bank of Canada, 2017)
This paper proposes a novel asymptotic least-squares estimator of multi-country Gaussian dynamic term structure models that is easy to compute and asymptotically efficient, even when the number of countries is relatively large - a situation in which other recently proposed approaches lose their tractability. We illustrate our estimator within the context of a seven-country, 10-factor term structure model.
Keywords: E43; F31; G12; G15; 330; Asset pricing; Econometric and statistical methods; Exchange rates; Interest rates